👤

bonjoour,
A = (– 8 + 12 – 5 + 7) × (11 – 13 – 7 – 2)
B = – 7 × 3 – 9 × (– 5) + (– 4) × 9 – 7
C = 6 – [– 4 × (– 3) + 5 × (– 2)] × (– 4)
Merci


Répondre :

Réponse :

Bonsoir,

A = (-8+12-5+7)*(11-13-7-2)

A = (19-13)*(11-22)

A = 6*(-11)

A = -66

B = -7*3-9*(-5)+(-4)*9-7

B = -21+45-36-7

B = 45-64

B = -19

C = 6-(-4*(-3)+5*(-2))*(-4)

C = 6-(12-10)*(-4)

C = 6-(2)*(-4)

C = 6-(-8)

C = 6+8

C = 14

bonjour

A =  6 x - 11 = - 66

B =  -  21 + 45 - 36 - 7 = - 19

C = 6 - [ 12  - 10 ) x - 4  =  6 - 2 x - 4 = 6 + 8 = 14